The splendour o f the truth in the Breviloquium o f Buenaventura (Iter, 2022)
The present study realices an interpretation o f the mentions o f truthin the Breviloquium o f Bonaventure. An analytic lecture o f a work thatpays attention o f the foundating origine of veritas, o f her presence in thehuman being, created as a image and resemble o f God, but deformed byguilty. The study, as well pays attention to the splendour o f that truth in thereformed image by God and her transformed situation between return andbeginning.
Keywords: Truth, theology, Bonaventure, Breviloquium, splendour